Procedure for Investigation and Accounting of Accidents in the Process of Activity in Production - Jalilovna, Kobulova Nilufar; Sattarovna, Jumanova Maxsudaxon (European Journal of Life Safety and Stability (2660-9630), 2022)
This article describes the procedure for investigation and accounting of accidents at industrial enterprises, measures to prevent accidents and occupational diseases, the main aspects of its implementation. Also, the social, economic, legal and technical effects of the safety regulations of manufacturing processes.